Efficient Sleep, Enhanced Attention: Exploring the Interplay With RBC-Inflammation Mechanisms in Hypoxic High-Altitude Areas - Shi CY; Xue XJ; Li ZF; Huang XY; Su R; Wang NN; Zhu JG; Li H; Ma HL; Liu M; Zhang DL (Nature and Science of Sleep)
Chun-Yan Shi,1,2 Xiao-Juan Xue,3 Ze-Feng Li,4 Xiao-Yan Huang,1,2 Rui Su,5,6 Nian-Nian Wang,1,2 Jin-Guo Zhu,1,2 Hao Li,5,6 Hai-Lin Ma,5,6 Ming Liu,1,2,5 De-Long Zhang1,2,5 1Key Laboratory of Brain, Cognition and Education Sciences, Ministry of Education, Guangzhou, Guangdong, People’s Republic of China; 2School of Psychology, Center for Studies of Psychological Application, Guangdong Key Laboratory of Mental Health and Cognitive Science, South China Normal University, Guangzhou, Guangdong, People’s Republic of China; 3Department of Experimental Clinical and Health Psychology, Ghent University, Ghent, Belgium; 4Department of Head and Skin, Ghent University, Ghent, Belgium; 5Plateau Brain Science Research Center, Tibet University and South China Normal University, Lhasa and Guangzhou, People’s Republic of China; 6Academy of Plateau Science and Sustainability, People’s Government of Qinghai Province and Beijing Normal University, Qinghai and Beijing, People’s Republic of ChinaCorrespondence: De-Long Zhang, School of Psychology, Center for Studies of Psychological Application, Guangdong Key Laboratory of Mental Health and Cognitive Science, South China Normal University, West No. 55, Zhongshan Avenue, Tianhe District, Guangzhou, 510631, People’s Republic of China, Tel +86-15920552874, Fax +86 020-85213411, Email delong.zhang@m.scnu.edu.cnPurpose: The complex interplay between sleep and attention, especially in the suppression of environmental information, is not well understood. This study investigates the bidirectional influence between sleep quality and executive control—an essential aspect of attention—and seeks to uncover the biological pathways involved in this relationship in hypoxic high-altitude areas.Patients and Methods: We recruited 140 han Chinese juniors from Tibet University, all originally from lowland areas. Participants underwent an attention network test with concurrent electroencephalography to assess attentional function. Sleep quality was evaluated using the Pittsburgh Sleep Quality Index, while the Symptom Check-List-90 and a standard physical examination measured overall health status. A breaking continuous flash suppression task gauged conscious perception breakthrough capacity.Results: Our findings reveal a bidirectional link between sleep quality and executive control function, which appears to be related to an inflammatory response associated with erythrocyte attributes. Specifically, the P1 and N1 orienting amplitudes mediated the effects of sleep on executive control. This relationship suggests that executive control may, in turn, regulate sleep patterns, with implications for mental health. We also found that enhanced sleep efficiency was correlated with a balance between alerting functions and executive control.Conclusion: The study establishes that sleep quality and executive control are interlinked via an inflammatory response related to red blood cell characteristics, impacting mental health. Better sleep correlates with improved cognitive performance, suggesting that sleep is crucial for optimal attention resource management and overall cognitive well-being. This enhances our knowledge of the biological foundations of the sleep-attention interaction.Keywords: plateau sleep, attention, erythrocyte, inflammation